The Role of Information and Communication Technology (ICT) in Enhancing the Innovative Learning Process - Adam, Frans; Ray, Gilbert (Pandawan Sejahtera Indonesia, 2020)
The most significant instruments in the learning cycle are the educator and learning media. Obviously, the utilization and choice of fitting instructional media completed by an instructor will have an impact on the cycle and consequences of the learning. For this situation, data and correspondence innovation based learning media is the most significant thing in the advancement of the universe of training. Data and Communication Technology (ICT) is a program for instruments, control and passing on of data and information to make it simpler in the learning cycle in the homeroom. With ICT-based learning media, understudies can create thinking abilities and improve instructor aptitudes expertly. Educators become more propelled and inventive in homeroom learning. The reason for this investigation was to decide the function of educators in utilizing learning media dependent on Information and Communication Technology.